Internalisasi Nilai-nilai Pendidikan Akhlak QS. Al-Furqan Ayat 63 di MTs Miftahul Ulum Rek Kerrek Laok Palengaan Pamekasan - Ali Wafa; Mohamad Thoyyib Madani; Mat Sahri; Megawati Fajrin; Fatimatus Zahroh (AL -ALLAM, 2022)
This study aims to describe and analyze the internalization of moral education values ​​contained in QS. Al-Fuqan verse 63 in MTs Miftahul Ulum Rk-Kerrk. The internalization of values ​​of moral education is an urgent matter to continue to be integrated in the learning process. These values ​​are in line with the regulations on character education. Until now, education has become a national discussion because of the many immoral acts of violence, especially among students and even college students. The research method used is qualitative. The data collection techniques of this research were in-depth interviews with informants; intensive observation and observation; and documentation study of relevant documents. The data analysis of this research is to reduce the data to accommodate some data that are considered relevant; presentation of data through relevant qualitative data; and drawing conclusions that lead to the final result. The result of this research is the internalization of QS moral education values. Al-furqan verse 63 is: through habituation of humility; habituation does not say dirty; through exemplary shaking hands; and the habit of reading the Koran before lessons. Constraints on internalizing the values ​​of QS moral education. Al-furqan verse 63 is: lack of awareness of students; lack of parental support; and the lack of binding rules from madrasas.